Ecbasis Cuiusdam Captivi Per Tropologiam-Escape of a Certain Captive Told in a Figurative Manner An Eleventh-Century Latin Beast Epic - Zeydel, Edwin H. (UNC Studies in the Germanic Languages and Literatures, 1964)
The oldest medieval beast epic was translated literally into English prose for the first time in this volume, with Latin on facing pages. The introduction and commentary by Zeydel familiarize the reader with the history and value of the text and constituted a new approach, arguing for the inclusion of Latin literature composed in what is now Germany in the history of German literature.